A Surface Approach to Learning Rewards First-Year Engineering Students - Svedin, M.; Balter, O.; Scheja, M.; Pettersson, K. (2013 Learning and Teaching in Computing and Engineering (LaTiCE), 2013)
In a study investigating first-year engineering students' approaches to learning and studying, a surface approach to learning was shown to be the best predictor of academic achievement. A strategic approach to studying was found to be a negative factor. A questionnaire was distributed to first-year students aiming for Master of Science in Engineering in either Computer Science or Media Technology in the beginning and the end of their first year of study. In the first instance 150 students (69.5 %) answered the questionnaire and 87 (34.5 %) participated on both occasions.